Study of Financial Management of Vannamei Shrimp Cultivation in Tasikharjo Village - Zakiya, Ardis Laily; Susilo, Agus (Universitas Muhammadiyah Surakarta, 2022)
This study aims to identify: 1) Forms of financial management for vannamei in Tasikharjo Village, and 2) Constraints and solutions to financial management problems for vannamei. This study uses a qualitative approach with the type of case study taking the research location in the village. Tasikharjo with shrimp cultivators as resource persons. Methods of data collection using interviews, observation, and documentation. The analysis technique uses data reduction analysis, data validity by triangulation, data presentation, and drawing conclusions. The research findings show: 1) The form of financial management of cultivators in business activities with funds sourced from internal and external, financial planning is carried out starting from pre-dispersal of seeds to the harvesting process and searching for market price information, there is no recording by business actors, reporting is used only profit/loss , then financial management is still mixed with family finances, and saving activities are carried out at the bank. 2) Financial management problems, business actors do not understand proper financial management and assume that there is no need for regular financial management because small businesses are not. The solution to financial management problems for business actors is to try to find a way out by asking their children for help to use financial applications on cellphones and controlling finances so they don't get mixed up with family finances.